Representasi Waria dalam Sinema Indonesia pada Masa Orde Baru Sampai Era Moral Panic - Febriyanti, Shabrina Farahiyah; Gietty, Shuri Mariasih; Rahmi, Rias Antho (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
The banning of transgender representation in the mainstream media by KPI has limit the way society is empowered on the issues concerning transgender in Indonesia. The development of transgender representation in the media are not as progressive as it could be without the banning from KPI. This research aims to investigate Betty Bencong Slebor (1978), Dulu Banci (2011), Aku Bukan Banci Kaleng (2012), Bias (2015), and On Friday Noon (2016) films in reference to representation theory to compare and contrast on how waria is represented during the New Order , post-reformation, and moral panic eras. Research findings reveal that films produced during the post-reformation period tend to perpetuate the stereotype of waria as it was constructed during the New Order era because of the government's refusal to classify waria as women. Furthermore, waria are often represented in the context of religious, spesifically Islamic, values. During the moral panic era, several stereotypes have actually been contested in the films even though stereotypes regarding waria’s appearance and job are still strongly discriminating. Keywords: identity; Indonesia cinema; KPI; representation; waria